2020
DOI: 10.1126/sciadv.aba7621
|View full text |Cite
|
Sign up to set email alerts
|

Residential solid fuel emissions contribute significantly to air pollution and associated health impacts in China

Abstract: Residential contribution to air pollution–associated health impacts is critical, but inadequately addressed because of data gaps. Here, we fully model the effects of residential energy use on emissions, outdoor and indoor PM2.5 concentrations, exposure, and premature deaths using updated energy data. We show that the residential sector contributed only 7.5% of total energy consumption but contributed 27% of primary PM2.5 emissions; 23 and 71% of the outdoor and indoor PM2.5 concentrations, respectively; 68% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 22 publications
5
143
2
1
Order By: Relevance
“…It was hard to investigate the long-term effect of PM 2.5 exposure increase in the annual festival days overlapping COVID-19 lockdown. For example, we could not estimate the PM 2.5 -associated premature deaths because it was estimated based on the whole life, not a short period ( Yun et al, 2020 ). While, some short-term effect such as asthma, blood pressure increase may be caused by the increase of PM 2.5 exposure in a relative short time considering the lockdown in rural China lasted for more than one month ( Wang et al, 2018 ; Williams et al, 2019 ; Chen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was hard to investigate the long-term effect of PM 2.5 exposure increase in the annual festival days overlapping COVID-19 lockdown. For example, we could not estimate the PM 2.5 -associated premature deaths because it was estimated based on the whole life, not a short period ( Yun et al, 2020 ). While, some short-term effect such as asthma, blood pressure increase may be caused by the increase of PM 2.5 exposure in a relative short time considering the lockdown in rural China lasted for more than one month ( Wang et al, 2018 ; Williams et al, 2019 ; Chen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that air quality inside the GBA can be improved from reductions in residential emissions outside the GBA, as pollution transport into the GBA is important. These reductions in residential emissions may be realized in North China from current policies, however, solid fuel use remains high in many rural areas of South China (Yun et al., 2020), where there are currently no specific policies to reduce residential emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Because we were not sure what the other fuel was, we excluded the users of other fuels and those that answered that they never cook. Considering a previous study on the health effects of fuel burning 21 , we defined cooking fuel as solid fuel (coal, crop residue and wood) and clean fuel (natural gas, marsh gas, liquefied petroleum gas and utilizing electricity).…”
Section: Methods and Measurementsmentioning
confidence: 99%